Writing Metacognitive Awareness and Writing Performance Anxiety among Senior High School Students at a Philippine University - Mark Joshua Roxas (Scientia Publica Media, 2025)
Strengthening senior high school learners’ oral and written language skills is a prominent focus of the K12 program. In this level, students encounter intricate writing concepts that necessitate advanced cognitive abilities. Hence, metacognitive awareness is crucial in scaffolding students’ development and understanding of complex writing skills and conventions. This study sought to assess the relationship between senior high school students’ writing metacognitive awareness and writing anxiety. Two adopted questionnaires—the Metacognitive Awareness Writing Questionnaire (MAWQ) by Farahian (2017), and the Second Language Writing Anxiety Inventory (SLWAI) by Cheng (2004) were administered to 120 senior high school students who were selected through convenience and availability sampling. The data were analyzed using descriptive statistics (frequency, percentage, and mean), and Spearman’s rho test of relationship. The results revealed that the respondents demonstrate a commendable degree of metacognitive awareness in various aspects of writing. The study further noted that the respondents experience anxiety in performing writing tasks. Their anxiety in writing impacts their metacognitive abilities, as the analysis showed a significant moderate positive monotonic relationship (rs = 0.36224, p (2-tailed) = 5E-05) between the respondents’ extent of writing metacognitive awareness and level of writing anxiety. Therefore, students who have a high extent of metacognitive awareness may experience a high level of writing anxiety, and vice versa. Anchored on the findings, the study recommends that teachers implement various strategies to support students in managing their anxiety during the writing process. These strategies can contribute to improving the overall writing experience for senior high school students.